Respons Genotipe Kedelai sebagai Tanaman Sela pada Tumpang Sari dengan Ubi Kayu - Titik Sundari; Purwantoro Purwantoro; Rina Artari; Yuliantoro Baliadi (Institut Pertanian Bogor, 2020)
Soybean development to intercropping is one of the opportunities to increase soybean planting area. Each soybean variety has different responses to intercropping so it is required to study soybean varieties that are suitable or adaptive to intercropping environments. Therefore, a research was conducted to determine the response of soybean genotypes in intercropping with cassava. The research was conducted at the Jambegede Research Station, Malang in February to December 2018, in two environments, namely intercropping (L1) and monoculture (L2), with two planting times, namely three weeks (T1) and 4 months (T2) after cassava planting. Twelve promising lines and three varieties (Dena 1, Dena 2, and Grobogan) were used as research materials. A completely randomized block design with three replications was used to arrange the treatments in each environment. The results showed that the responses of each soybean genotype tested as intercrops on intercropping system with cassava were varied, depending on the soybean planting time. GH-5 and GH-6 soybean genotypes are suitable for the first intercrop (T1), while GH-3 are suitable as the second intercrops (T2) in intercropping system with cassava + Soybean, with higher stress tolerance index (STI) and lower weighted sensitivity index (WSI) than the other genotypes tested. Based on the land equivalent ratio (LER), intercropping of cassava with GH-5, GH-6, or GH-3 soybean genotypes was advantageous (RKL>1.0). Keywords: land equivalent ratio, stress tolerance index, weighted sensitivity index